Fluctuations in emergency department visits related to acute otitis media are associated with extreme meteorological conditions - Nieratschker, Michael; Haas, Markus; Lucic, Mateo; Pichler, Franziska; Brkic, Faris F.; Parzefall, Thomas; Riss, Dominik; Liu, David T. (Frontiers in Public Health, 2023)
Background: Climate change has been associated with a higher frequency of extreme weather events, resulting in an overall increase in morbidity and mortality. Acute otitis media (AOM) is one of the most common otolaryngological infections and accounts for 1.5% of emergency department visits. This study aimed to identify associations between extreme weather events and the immediate and delayed risks for AOM-related emergency department visits (EV). Methods: A total of 1465 AOM-related EVs were identified in the Vienna General Hospital between 2015 and 2018. A distributed lag non-linear model was applied to evaluate the relationship between extreme weather conditions and the total number of AOM-related EVs per day. The relative risk (RR) and cumulative RR (cRR) of single-day events and extended weather events over three days were analyzed over a lag period of 14 days. Results: AOM-related EVs showed a pronounced seasonality, with the highest occurrence during winter. Single-day weather events affected AOM-related EVs only at high relative humidity. Prolonged extreme weather conditions over three days, however, significantly increased the cRR for AOM-related EVs to 3.15 [1.26-7.88; p=0.014] and 2.14 [1.14-4.04; p=0.018] at mean temperatures of -4°C (1st-percentile - p1) and 0°C (p5) on the same day. Relative humidity of 37% (p1) decreased RR to 0.94 [0.88-0.99; p=0.032] on day 7, while extremely high humidity of 89% (p99) led to an increased cRR of 1.43 [1.03-2.00; p=0.034] on day 7. Heavy prolonged precipitation of 24mm (p95) reduced cRR beginning day 4 up until day 14 to 0.52 [0.31-0.86; p=0.012]. Prolonged low atmospheric pressure events of 985hPa (p5) reduced the RR to 0.95 [0.91-1.00; p=0.03], whereas extremely high atmospheric pressure events of 1013hPa (p99) increased the RR to 1.11 [1.03-1.20; p=0.008]. Extremely low wind speeds significantly diminished the RR of AOM-related EVs. Conclusions: While single-day extreme weather events had little impact on the occurrence of AOM-related EVs, extended periods of extreme temperatures, relative humidity, precipitation, wind speeds and atmospheric pressure significantly impacted the RR for AOM-related EVs. These findings could help improve healthcare resource allocation in similar climates and aid in educating patients about the role of environmental factors in AOM.